Determination of amino acid motifs present in the antigen-binding site of BoLA-DRB3 alleles in a Holstein population of La Pampa y su asociación con mastitis (Veterinary Science, 2017)
The intensity of the immune responseis regulated by amino acid motifs in antigen recognitionsites (ARS) present in the pockets ofMajor Histocompatibility Complex molecules.The objective of this work was to study the associationbetween these motifs and resistance/susceptibility to mastitis measured by somaticcell counts (SCC) in milk from Holstein cattlefrom the province of La Pampa. The populationwas divided into: 1) case group with high SCCand presence of mastitis (≥ 250,000 cells/mlsusceptibility) and 2) control group under SCC(< 250,000 cells/ml resistant). From a sample of128 animals, 40 were genotyped for the secondexon of BoLA-BRB3 gene by direct sequencingtechnique, 20 cows for each group. A total of 24alleles were detected in the analyzed population.Gene frequencies of amino acid motifs ofthe five pockets (1, 4, 6, 7 and 9) from ARS inthe two groups of animals were calculated. TestOdds Ratio (OR) Woolf-Haldane was used tostudy the association. No significant differencesbetween amino acid motifs of pockets 1, 4, 7and 9 between groups with high and low SCCwere found. However, the T 11 Y 30 motif inpocket 6 (found in BoLA-DRB3 * 0601, * 0901and * 4401 alleles) showed a significant ORvalue = 0.11 (p = 0.03). This suggests an associationbetween this motif with a lower risk ofdeveloping mastitis. The role of amino acid motifT 11Y 30 in animal immune response should bevalidated in independent populations
Keywords: amino acid motifs; mastitis; immune response; BoLA-DRB3; Holstein